Effect of Directional Deep Brain Stimulation on Sensory Thresholds in Parkinson’s Disease - Sabourin, Shelby; Khazen, Olga; DiMarzio, Marisa; Staudt, Michael D.; Williams, Lucian; Gillogly, Michael; Durphy, Jennifer; Hanspal, Era K.; Adam, Octavian R.; Pilitsis, Julie G. (Frontiers in Human Neuroscience, 2020)
Objective:. Previous studies showed that deep brain stimulation(DBS) relieves pain symptoms in Parkinson Disease(PD) patients when programmed for motor-symptom relief. One factor involved in pain processing is sensory perception of stimuli. With the advent of directional leads, we explore whether directional DBS affects quantitative sensory testing(QST) metrics acutely. Methods: PD patients with subthalamic(STN) DBS and directional leads were tested in 5 settings(DBS-OFF, DBS-ON with omnidirectional stimulation, and DBS-ON) for each of 3 directional segments of contact used for clinical programming. The Unified Parkinson’s Disease Rating Scale(UPDRS-III) assessed patient's motor skills at time of study visit at clinical contact and at contact which produced optimal sensory threshold(defined by the greatest tolerance to mechanical stimuli). Correlation analyses were performed between stimulation parameters(amplitude, frequency, pulse width(PW), total electrical energy delivered(TEED)) and outcome metrics. Results: Sensory thresholds were obtained in 9 patients. Directional stimulation did not significantly alter patient perceptions of sensory stimulus(cold pain(p=0.69), warm pain(p=0.99), Von frey fibers(p=0.09), pin-prick(p=0.88), vibration(p=0.40), pressure(p=0.98)). With correlation analysis, increasing PW at the posterior contact increased pin prick and vibration sensitivity(p<0.001). Additionally, an increase in TEED caused a decrease in sensitivity to warm detection when using the anterior(p=0.04), lateral(p=0.02) and medial contacts(p=0.03), and also caused a decrease in sensitivity to cold detection when using the medial contact(p=0.03). UPDRS-III remained stable during testing. Conclusions: Motor benefit can be acutely maintained at directional contacts, whereas directional stimulation can modulate thermal and mechanical sensitivity. Further investigation will determine whether these changes are maintained chronically or can be improved with optimized programming.